MATHEMATICS AND ITS TEACHING IN THE MUSLIM WORLD - Vogeli, Bruce R. (Bruce Ramon); Tom, M. E. A., 1941- (Series on mathematics education, 2020)
This anthology reviews the history, current states, and plans for the development of mathematics education in the Muslim States in Africa, the Middle East, and Asia. There is an introduction by Ahmed Djebbar, the most prominent contemporary scholar of Muslim mathematics. The chapters are written by respective national experts in mathematics education.